Evaluation and Analysis of Factors Affecting the Development of Coastal Tourism (Study Case: Manjil Coastal City) - Farzaneh Dehghani Gishi; Soude Noormohammadi; Milad Babayi Elyasi; Narjes Sadat Barakbaf (توسعه پایدار شهری)
The purpose of this research is to evaluate and analyze the factors affecting the development of coastal tourism in Manjil city and to provide solutions for the development of the tourism industry in this region. The research method is applied in terms of purpose and research methodology is descriptive-analytical. In order to collect the required information and data, library and field methods were used. The statistical community in the current research was formed by professors and doctoral students of geography, urban planning and urban planning, experts and specialists in the field of tourism in Gilan province and Manjil city, who had sufficient knowledge of tourism and Manjil city. Also, the sample size based on Sample Power software, 30 people who were available were selected. In order to collect field data, a questionnaire tool was used, the validity of which was confirmed by experts in terms of content and appearance. In this research, in order to analyze the data, Pearson's correlation coefficient and Friedman's ranking tests were used in the SPSS software environment. The results of the research showed that among the factors affecting the development of coastal tourism in Manjil city, except for the social-behavioral and managerial-institutional components, as well as the social-behavioral and environmental components, which have a weak significant relationship between them, there is a positive and significant relationship in other components. In other words, the highest degree of correlation between economic and managerial-institutional components is (0.726) and the lowest degree of correlation is between social-cultural and managerial-institutional components (0.256). Also, by using Friedman's test, it was determined that the economic component with a total average of 2.206 is in the worst situation compared to other components of the research, and it is necessary for the managers and officials of Manjil city to make more efforts to improve this index.